Ethanol Extract of Pomegranate (Punica granatum) Peel in Increasing the Expression of Caspase-3 in DSS-Induced Mice - Kusmardi Kusmardi; Lyanna Azzahra Baihaqi; Ari Estuningtyas; Nurhuda Sahar; Hadi Sunaryo; Aryo Tedjo (Hindawi Limited, 2021)
Background. Colorectal cancer (CRC) is a malignancy derived from the glandular epithelial cells in the colon. Patients with inflammatory bowel disease (IBD) are more likely to develop CRC. Cancer proliferation is characterized by the loss of inhibition of apoptosis, which involves caspase-3 activation. This study examined the effects of the pomegranate peel extract on the expression of caspase-3 in mice crypt cells induced by dextran sodium sulfate (DSS) 2%. Methods. The experimental study was done in six groups. All treatments were done in 42 days. The groups were all induced by DSS through water drinking, except for the normal group, which was only given water. The treatments given included the pomegranate extract in two doses (240 mg and 480 mg/kg bw/day), aspirin, and ellagic acid. The specimens were then fixated and stained for the immunohistochemistry scoring for the expression of caspase-3, which was then analyzed statistically. Results. The H-scores of each treatment group were 213.23 ± 8.32 (DSS group), 243.81 ± 18.69 (normal group), 226.10 ± 12.38 (pomegranate peel extract of 240 mg/kg/d), 238.84 ± 15.81 (pomegranate peel extract of 480 mg/kg/d), 227.47 ± 12.15 (aspirin), and 224.01 ± 18.39 (ellagic acid). Statistical differences were found in one-way analysis of variance (ANOVA) and post hoc analysis among the DSS group, normal group, and dose 2 group (pomegranate peel extract of 480 mg/kg/day). Conclusions. The ethanol extract of pomegranate was able to induce apoptosis, which was demonstrated by the increase of caspase-3 expression.